Do Ties Really Bind? The Effect of Knowledge and Commercialization Networks on Opposition to Standards - Ranganathan, Ram; Rosenkopf, Lori (Academy of Management Journal, 2014)
We examine how the multiplicity of interorganizational relationships affects strategic behavior by studying the influence of two such relationships—knowledge linkages and commercialization ties—on the voting behavior of firms in a technological standards-setting committee. We find that, while centrally positioned firms in the knowledge network exhibit lower opposition to the standard, centrally positioned firms in the commercialization network exhibit higher opposition to the standard. Thus, the influence of network position on coordination is contingent upon the type of interorganizational tie. Furthermore, when we consider these relationships jointly, knowledge centrality moderates the opposing effect of commercialization centrality, such that the commercialization centrality effect increases with decreasing levels of knowledge centrality. In other words, firms most likely to delay the standard are peripheral in the knowledge network yet central in the commercialization network, which suggests that they have the most to lose from changes to current technology.